Формування іншомовної комунікативної компетентності правоохоронців в освітньому середовищі закладу вищої освіти із специфічними умовами навчання - Марченко, О. Г.; Marchenko, O. H.; Сидоренко, І. І.; Sydorenko, I. I.; Ольга Марченко (Науковий часопис НПУ імені М. П. Драгоманова. Серія 5: Педагогічні науки: реалії та перспективи. - 2022. - Вип. 89. - С. 107-112, 2022)
Проаналізовано можливості освітнього середовища закладу вищої освіти щодо формування іншомовної комунікативної компетентності правоохоронців. З’ясовано, що серед чисельних компонентів освітнього середовища найбільш впливовими щодо формування іншомовної комунікативної компетентності правоохоронців є змістовий (інформаційне поле для задоволення освітніх потреб комунікаторів), комунікативний (комфортна емоційно-психологічна атмосфера, яка допомагає курсантам долати мовні та психологічні бар’єри іншомовного спілкування), організаційно-управлінський (матеріально-технічне та навчально-технологічне підґрунтя освітнього процесу, запровадження інформаційно-комунікаційних технологій у навчанні іншомовному професійному спілкуванні).

The article substantiates the relevance of the problem of the formation of foreign language communicative competence of law enforcement officers as an integral component of their professional competence based on the theoretical and source base, analyses of empirical quantitative and qualitative material substantiated the relevance of the problem of formation of foreign language communicative competence of law enforcement officers as an integral component of their professional competence. Foreign language communicative competence of law enforcement officers is characterized as a professional formation that integrates the presence of certain life values, attitudes (axiological component), knowledge and adequate use of language tools (cognitive component), speech and communication skills (activity component), personal qualities necessary for effective foreign language professional communication. Favorable and inhibiting factors influencing the course of the researched process at content-professional, corporate-ethical, personal-cultural levels were determined. It has been proven that foreign language professional communication is basic for the formation of foreign language communicative competence of law enforcement officers. It is shown that the organization of effective foreign language professional communication involves the formation of an educational environment with given parameters. The educational environment of a legal institution of higher education is characterized as a set of specific learning conditions affecting the spatial and functional spatial association of subjects of educational activity, between which close, diverse, individual and group, formal and interpersonal relationships are established and personal, educational, service, professional needs, interests, abilities of communicators. The possibilities of the educational environment of the institution of higher education regarding the formation of foreign language communicative competence of law enforcement officers have been analyzed. It was found that among the numerous components of the educational environment, the most influential in the formation of foreign language communicative competence of law enforcement officers are content (information field to meet the educational needs of communicators), communicative (a comfortable emotional and psychological atmosphere that helps cadets overcome linguistic and barriers of foreign language communication), organizational and administrative (material-technical and educational-technological basis of the educational process, introduction of information and communication technologies in teaching foreign language professional communication). In the future, it is planned to clarify the criteria and indicators, the dynamics of the levels of formation of the foreign language communicative competence of law enforcement officers as a result of experimental verification of the influence of the educational environment of the institution of higher education of the legal profile.

Проанализированы возможности образовательной среды высшего образования по формированию иноязычной коммуникативной компетентности правоохранителей. Выяснено, что среди многочисленных компонентов образовательной среды наиболее влиятельными относительно формирования иноязычной коммуникативной компетентности правоохранителей является содержательный (информационное поле для удовлетворения образовательных потребностей коммуникаторов), коммуникативный (комфортная эмоционально-психологическая атмосфера, которая помогает курсантам преодолевать речевые и психологические барьеры иноязычного общения), организационно-управленческий (материально-техническая и учебно-технологическая основа образовательного процесса, внедрение информационно-коммуникационных технологий в обучении иноязычному профессиональному общению).
Formation of another language communicative competence of law officers in the educational environment of a higher education institution with specific learning conditions
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; заклади вищої освіти зі специфічними умовами навчання; institutions of higher education with specific study conditions; заведения высшего образования со специфическими условиями обучения; іншомовна комунікативна компетентність; foreign language communicative competence; иноязычная коммуникативная компетентность; професійне спілкування; professional communication; профессиональное общение; правоохоронці; law enforcement officers; правоохранители; освітнє середовище; educational environment; образовательная среда